Relationship Between Grade 7 Students’ Interest and Their Performance in Acid-Base Lessons Using LoLiPap and CIS - Benong, Christopher Bernard; Benong, Shery-Ann; Piñero, Brando; Futalan, Maria Chona (Journal of Interdisciplinary Perspectives, 2024)
This study utilized descriptive, correlational, and cluster-randomized controlled trial (CRT) methods to explore the relationship between the Grade 7 students’ interest and their performance in learning acid-base lessons using localized litmus paper (LoLiPap) and a computer interactive simulator (CIS) at a private school in Dumaguete City (SY 2023-2024). Validated questionnaires were used to assess the students’ interests and performance. As indicated by the results, the two groups of students exhibited a "very high" interest in using the LoLiPap and CIS methods and attained "fairly satisfactory" performances. It was further unveiled that the interest levels of both groups, with p-values of 0.243 and 0.064, respectively, were not significantly related to their performance. This finding suggests that, besides interest, other factors affect students’ learning outcomes. It is advised that the two methods should be combined with effective classroom dynamics, positive teacher behavior, better study habits, and a supportive environment to improve student performance.